Case Study Evaluation of Steel Girder of Bridge Replacement by GFRP - Arashnia, Parinaz; Ghaffarpour Jahromi, Saeed; Hatami, Farzad (International Journal of Sustainable Construction Engineering and Technology, 2015)
Nowadays, because of the steel desired tensile, compressive strength, and light weight especially in the large spans, it has been widely popular in the bridge construction. On the other hand, there are some disadvantages including corrosion, buckling and weaknesses in the higher temperatures, and unsuitable weld which would be resolved using Fibres Reinforced Polymer (FRP) profiles. The FRP is a remarkable class of composite polymers that can improve structural elements behaviours like as resistance against corrosion, fire, electricity, and magnetic fields. In this paper, composite GFRP & UHF beams along with the behaviour of I-shaped beam were studied and discussed under the point loads using numerical models, results were compared and verified with the experimental tests whereas two different beams were modelled and verified under static progressive loading performed with ABAQUS as an FEM base software. Finally, Moddares-Haqqani that is a steel girder bridge has been modeled by SAP software and maximum displacement has been determined. Then 4 GFRP beams modeled by ABAQUS software and best section has been determined. Beams are under dead and live loading. Purposes of this paper are evaluating of use of GFRP materials as a basic material in construction process and compare this operation with steel. Results shown that because of lower modulus of elasticity in GFRP compare with steel, displacement has increase in GFRP beams and hence beams dimension must be increase to limit displacement.